How policy implementation shapes the impact of U.S. food assistance policies: the case study of the Child and Adult Care Food Program - Kenney, Erica L.; Poole, Mary Kathryn; Frost, Natasha; Kinderknecht, Kelsey; Mozaffarian, Rebecca S.; Andreyeva, Tatiana (Frontiers in Health Services, 2023)
Much of the chronic disease burden in the U.S. population can be traced to poor diet. There has been a sustained focus on influencing children's diets and encouraging healthier eating habits by changing policies for what foods and beverages can be served to children through large federally-funded nutrition assistance programs. Yet without attention to how nutrition policies are implemented, and the surrounding context for these policies, these policy changes may not have the intended results. In this perspective, we used Bullock et al.'s (2021) Process Model of Implementation from a Policy Perspective to analyze how the complexities of the implementation process of large-scale nutrition policies can dilute potential health outcomes. We examine the Child and Adult Care Food Program (CACFP), a federal program focused on supporting the provision of nutritious meals to over 4 million children attending childcare, as a case study. We examine how the larger societal contexts of food insecurity, attitudes towards the social safety net, and a fragmented childcare system interact with CACFP. We review the “policy package” of CACFP itself, in terms of its regulatory requirements, and the various federal, state, and local implementation agencies that shape CACFP's on-the-ground implementation. We then review the evidence for how each component of the CACFP policy implementation process impacts uptake, costs, feasibility, equity, and effectiveness at improving children's nutrition. Our case study demonstrates how public health researchers and practitioners must consider the complexities of policy implementation processes to ensure effective implementation of nutrition policies intended to improve population health.